ANTIMICROBIAL RESISTANCE PATTERNS IN PAEDIATRIC PATIENTS: A RETROSPECTIVE ANALYSIS OF MICROBIAL ISOLATES AND ANTIBIOTIC SUSCEPTIBILITY - Linda Pinky; Nokukhanya Thembane (Student's Journal of Health Research, 2023)
Introduction: This study aimed to determine the frequency and antibiotic resistance patterns of various organisms isolated from paediatric samples in a South African hospital. Antibiotic resistance is a growing concern in healthcare, particularly in paediatric patients more vulnerable to infections. It was conducted in an attempt to address the lack of data on the prevalence of antibiotic-resistant organisms in South African paediatric patients. Methodology: A retrospective study was conducted on the microbiological results of paediatric samples obtained between 2017 and 2018 at a tertiary hospital in South Africa. Organisms were identified using standard microbiological techniques, and their antibiotic susceptibility patterns were determined using the Kirby-Bauer disc diffusion and Vitek method. Results: Of the 165 organisms isolated, the most common were Acinetobacter baumannii (20.6%), Klebsiella pneumoniae (16.3%), and Enterobacter cloacae (10.9%). High rates of resistance were observed to commonly used antibiotics, including amikacin, ciprofloxacin, and augmentin. Candida albicans and Candida spp. showed high resistance rates to fluconazole. Conclusion and recommendation: This study underscores the importance of continued surveillance of antibiotic resistance patterns in pediatric patients in South Africa. The high prevalence of antibiotic-resistant organisms and limited treatment options emphasize the need for implementing antibiotic stewardship programs, strengthening infection control measures, and conducting ongoing surveillance. Additionally, investment in research and development, along with promoting education and awareness, is crucial for effectively managing antimicrobial resistance in this population. These recommendations will guide the selection of empiric therapy and aid in the development of antibiotic stewardship programs in South African hospitals.